Intermediate filaments spatially organize intracellular nanostructures to produce the bright structural blue of ribbontail stingrays across ontogeny - Blumer, Michael J.; Surapaneni, Venkata A.; Ciecierska-Holmes, Jana; Redl, Stefan; Pechriggl, Elisabeth J.; Mollen, Frederik H.; Dean, Mason N. (Frontiers in Cell and Developmental Biology, 2024)
In animals, pigments but also nanostructures determine skin coloration, and many shades are produced by combining both mechanisms. Recently, we discovered a new mechanism for blue coloration in the ribbontail stingray Taeniura lymma, a species with electric blue spots on its yellow-brown skin. Here, we characterize finescale differences in cell composition and architecture distinguishing blue from non-blue regions, the first description of elasmobranch chromatophores and the nanostructures responsible for the stingray's novel structural blue, contrasting with other known mechanisms for making nature's rarest color. In blue regions, the upper dermis comprised a layer of chromatophore units, iridophores and melanophores entwined in compact clusters framed by collagen bundles, this structural stability perhaps the root of the skin color's robustness. Stingray iridophores were notably different from other vertebrate lightreflecting cells in having numerous fingerlike processes, which surrounded nearby melanophores like fists clenching a black stone. Iridophores contained spherical iridosomes enclosing guanine nanocrystals, suspended in a 3D quasi-order, linked by a cytoskeleton of intermediate filaments.We argue that intermediate filaments form a structural scaffold with a distinct optical role, providing the iridosome spacing critical to produce the blue color. In contrast, black-pigmented melanosomes within melanophores showed space-efficient packing, consistent with their hypothesized role as broadband-absorbers for enhancing blue color saturation. The chromatophore layer's ultrastructure was similar in juvenile and adult animals, indicating that skin color and perhaps its ecological role are likely consistent through ontogeny. In non-blue areas, iridophores were replaced by pale cells, resembling iridophores in some morphological and nanoscale features, but lacking guanine crystals, suggesting that the cell types arise from a common progenitor cell. The particular cellular associations and structural interactions we demonstrate in stingray skin suggest that pigment cells induce differentiation in the progenitor cells of iridophores, and that some features driving color production may be shared with bony